Further evidence of biallelic NAV3 variants associated with recessive neurodevelopmental disorder with dysmorphism, developmental delay, intellectual disability, and behavioral abnormalities - Naseebullah Kakar; Selinda Mascarenhas; Asmat Ali; Azmatullah; Syed M. Ijlal Haider; Vaishnavi Ashok Badiger; Mobina Shadman Ghofrani; Nathalie Kruse; Sohana Nadeem Hashmi; Jelena Pozojevic; Saranya Balachandran; Mathias Toft; et al. (Human Genetics, 2025)
Neuron navigators (NAVs) are cytoskeleton-associated proteins well known for their role in axonal guidance, neuronal migration, and neurite growth necessary for neurodevelopment. Neuron navigator 3 (NAV3) is one of the three NAV proteins highly expressed in the embryonic and adult brain. However, the role of the NAV3 gene in human disease is not well-studied. Recently, five bi-allelic and three mono-allelic variants in NAV3 were reported in 12 individuals from eight unrelated families with neurodevelopmental disorder (NDD). Here, we report five patients from three unrelated consanguineous families segregating autosomal recessive NDD. Patients have symptoms of dysmorphism, intellectual disability, developmental delay, and behavioral abnormalities. Exome sequencing (ES) was performed on two affected individuals from one large family, and one affected individual from each of the other two families. ES revealed two homozygous nonsense c.6325C > T; p.(Gln2109Ter) and c.6577C > T; p.(Arg2193Ter) and a homozygous splice site (c.243 + 1G > T) variants in the NAV3 (NM_001024383.2). Analysis of single-cell sequencing datasets from embryonic and young adult human brains revealed that NAV3 is highly expressed in the excitatory neurons, inhibitory neurons, and microglia, consistent with its role in neurodevelopment. In conclusion, in this study, we further validate biallelic protein truncating variants in NAV3 as a cause of NDD, expanding the spectrum of pathogenic variants in this newly discovered NDD gene.

Exome sequencing in four families with neurodevelopmental disorders: genotype–phenotype correlation and identification of novel disease-causing variants in VPS13B and RELN - Tehseen Ullah Khan Afridi; Ambrin Fatima; Humayoon Shafique Satti; Zaineb Akram; Imran Khan Yousafzai; Wajahat Bin Naeem; Nasreen Fatima; Asmat Ali; Zafar Iqbal; Ayaz Khan; Muhammad Shahzad; Chunyu Liu; et al. (Molecular Genetics and Genomics, 2024)

Targeted hydrolysis of native potato protein: A novel workflow for obtaining hydrolysates with improved interfacial properties - Simon Gregersen Echers; Ali Jafarpour; Betül Yesiltas; Pedro J. García-Moreno; Mathias Greve-Poulsen; Dennis K. Hansen; Charlotte Jacobsen; Michael Toft Overgaard; Egon Bech Hansen (Food Hydrocolloids, 2023)